PENGARUH LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK - Yedija Revan Naibaho; Paul E. Sudjiman (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
The purpose of this research was to determine and analyze the effect of liquidity and firm size on the tax aggressiveness. This research is quantitative and uses secondary data take from annual reports of healthcare in the pharmacy and health research sub sector which exist on Indonesia Stock Exchange (BEI) during the period 2017-2020 period with the sample of 32 data from annual reports of pharmacy and health research companies using the purposive sampling method and using SPSS 24 tool. The results of this research partially concluded that liquidity and firm size have a negative effect on tax aggressiveness and simultaneously have an effect of 12.7% only.